Key Pillars in Storytelling to Generate Emotional Branding - Mera-Reategui, Adriana (2024)
Emotions are important when it comes to creating strong and lasting bonds between the target and the brands; therefore, storytelling and emotional branding need to be part of marketing strategies. This study aims to identify which emotions and which pillars are key in the storytelling of the spot “Amarás, única como tu pelo y tu Perú” (Amaras, unique as your hair and your Peru) to generate emotional branding. This research is located within the phenomenological paradigm with a qualitative methodology. The sampling technique was for convenience. Twenty-one female psychology students from Federico Villarreal Public University (UNFV), with ages ranging from 22 to 26. The emotions conveyed by the participants were joy, pride in being Peruvian, curiosity, strength, surprise, motivation, nostalgia, sensitivity and calmness. In terms of emotional branding, three key pillars that helped to attain an emotional connection with the students were identified. Three key pillars were identified for the students to achieve closeness with the brand: customer experience, brand authentic self, and warm glow. As a conclusion, the brand's storytelling evokes positive emotions in the students and identifies them as Peruvian.